Euclea natalensis Suppresses Postprandial Hyperglycemia in Rats via the Inhibition of α-Glucosidase: In vitro, in vivo, and Molecular Docking Studies - Bati, Keagile; Majinda, Runner R.T; Gaobotse, Goabaone; Kwape, Tebogo E. (Current Traditional Medicine, 2025)
BackgroundPostprandial hyperglycemia is a key factor in type 2 diabetes, and its management is critical in alleviating the deleterious consequences of diabetes and its associated micro and macrovascular complications.ObjectiveThe current study aims to determine the effect of Euclea natalensis leaf extracts on α-glucosidase inhibition in vitro and postprandial hyperglycemia in vivo in rats.MethodsSequentially extracted leaf extracts of Euclea natalensis were evaluated for their inhibitory effects on α-glucosidase in vitro and the suppression of postprandial hyperglycemia in normoglycemic rats. The extracts were fingerprinted using a Fourier-transform infrared (FTIR) spectroscopy (FTIR), and the bioactive compounds were evaluated by molecular docking for their interaction with α-glucosidase.ResultsFTIR fingerprinting of the extracts showed that they contain functional groups of important bioactive phytochemicals. The extracts inhibited α-glucosidase in vitro, with the methanol extract (1 mg/mL) showing the highest inhibitory effect of 93.52 ± 1.50% compared to 69.62% ± 1.45 of the standard drug acarbose (0.05 mg/mL). The extracts also reduced postprandial hyperglycemia in rats in a sucrose tolerance test, where the hexane and methanol extracts performed similarly to Acarbose. Molecular docking studies showed that 20 (29)-lupene-3β-isoferulate 3 is the most potent α-glucosidase inhibitor with the lowest binding energy of -10.79 kcal/mol, 2 hydrogen bonds with residues ASP1526 and ASP1157, and numerous van der Waals interactions with amino acids in the binding pocket of α-glucosidase.ConclusionEuclea natalensis leaf extracts were found to suppress postprandial hyperglycemia by inhibiting α-glucosidase activity; thus, it has a promising potential for use as an antidiabetic agent.
Keywords: postprandial hyperglycemia